Differences in rectus femoris activation among skaters wearing fabric speed skating suits with different levels of compression - Moon, Y.-J.; Song, J.-H.; Hwang, J. (Korean Journal of Sport Biomechanics, 2016)
Objective: The purpose of this study was to investigate how different levels of compression exerted on the femoral region (known as the power zone) by coated fabric influences the activation and anaerobic capacity of the rectus femoris.